Literature Review : Pengembangan Booklet Peserta Didik SMA pada Pembelajaran Biologi - Mikra, Dini Pebrianti; Razak, Abdul; Syamsurizal; Rahmatika, Helsa (Jurnal Biogenerasi, 2024)
Education is a deliberate and unintentional effort to facilitate students in realizing their abilities to become professionals. The application of the learning process with the right techniques will achieve educational goals. Learning media can help the learning process to make it easier for educators to convey information. Learning media that are in accordance with the needs of learning activities will create effective and efficient learning activities. Developing booklets can be one of the effective and efficient learning media to attract students' interest and motivation in the learning process. Booklets contain pictures, outlines or interesting data that can support students' understanding who may interpret the material introduced by the teacher. The purpose of this literature review is to determine the effectiveness or feasibility of booklets that can be used in the learning process. The literature review includes 10 articles published in 2017-2023 that meet the criteria for research objectives. The results of the study show that booklets that can be used in the learning process are booklets that have valid or very valid criteria. Thus, the booklet can attract interest and motivation and understanding of students in the learning process